1995
DOI: 10.2307/146232
|View full text |Cite
|
Sign up to set email alerts
|

Baby Boomers and Their Parents: How Does Their Economic Well-Being Compare in Middle Age?

Abstract: We use survey data to compare the income and consumption of baby boomers in 1989 with that of their parents' generation in the early 1960s when they were the same ages. Various adjustments allow for changes in household composition and living arrangements. We also assess how wealth accumulation by baby boomers compares to that of their parents' generation. We find that boomers on average have accumulated more wealth relative to income at this point in their lives than their parents' generation had at the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 7 publications
(8 reference statements)
0
14
0
Order By: Relevance
“…These patterns suggest that young single male and female baby boomers may have had more income to invest and to accumulate wealth. Moreover, the increased earnings of the young female baby boomers may help lessen the gender gap in wealth (Manchester 1993;John Sabelhaus and Joyce M. Manchester 1995).…”
Section: Incomementioning
confidence: 99%
“…These patterns suggest that young single male and female baby boomers may have had more income to invest and to accumulate wealth. Moreover, the increased earnings of the young female baby boomers may help lessen the gender gap in wealth (Manchester 1993;John Sabelhaus and Joyce M. Manchester 1995).…”
Section: Incomementioning
confidence: 99%
“…In addition, the generation that grew up during the Depression has exhibited rather traditional gender roles and low levels of female labor force participation, high fertility rates, low divorce rates, and low levels of educational attainment compared to subsequent generations. As a result of work and family patterns, the Great Depression generation was likely to have less income than their children to save for retirement (Sabelhaus & Manchester, 1995). One potential outcome of conservative investing and low saving is that their children, whose behavior has diverged in important ways, may have accumulated more wealth during their working years and thus may have more funds available for retirement (Keister, 2000a).…”
Section: The Wealth Of Baby Boomers and Their Parentsmentioning
confidence: 99%
“…The baby boom generation has put pressure on social and economic resources at every stage of their lives. This cohort strained educational resources in the 1950s and 1960s as they filled classrooms to capacity, caused crowding in colleges and universities in their late teens and early 20s, and contributed to slow wage growth in the 1970s and 1980s when they entered the labor force (Sabelhaus & Manchester, 1995). In the 1990s, the changing age structure of the population, the financial condition of the social security system, and post–World War II declines in household saving have raised questions about whether this generation will have adequate resources to finance retirement (Levy & Michel, 1991; Longman, 1987).…”
mentioning
confidence: 99%
“…At $493,700, the inflation-adjusted mean net worth of early boomers is 32% higher for early boomers than it is for pre-boomers at the same age ($375,100), making it easy to conclude, as others have (Easterlin et al, 1993;Keiser, 2000;Sabelhaus & Manchester, 1993), that the boomer generation as a whole is better off than the prior generation. But, averages do not capture individual experience.…”
Section: Resultsmentioning
confidence: 99%
“…One line of research has found that, except for those with low levels of education or nonhomeowners, boomers have more financial resources than their parents, however the savings rate for both generations is about the same (Easterlin, Schaeffer, & Macunovich, 1993;Sabelhaus & Manchester, 1993). Easterlin et al (1993) cite lower fertility rates and women's increased labor force participation as the main reasons for boomer financial gains.…”
Section: Boomer Retirement Income Adequacymentioning
confidence: 99%